Video Conferencing Solutions for Students - Future Teachers' Professional Socialization - Roman S. Nagovitsyn; Roza A. Valeeva; Liliya A. Latypova (National Research Mordova State University, 2022)
Introduction. Despite the numerous publications on the implementation of distance technologies, there are practically no studies on the systematic analysis of various forms of video conferencing that support educational technologies and serve as a practical guide for teachers in teacher training. The purpose of the study is to analyze the experience of implementing video conferencing in various forms of interaction, to identify and experimentally test the effectiveness of their implementation in the process of professional socialization of student teachers. Materials and Methods. The study was conducted on the basis of the method of reflexive-system analysis of the implementation of video conferencing in the professional training of student teachers. Based on the questionnaire and the method of expert assessments, testing of the level of social and psychological adaptability, professional and behavioral skills, social and emotional comfort of students was implemented. The experiment involved 209 students of the Glazov State Pedagogical Institute and Kazan Federal University. Results. As a result of the study, it was revealed that the implementation of the group form of video conferencing significantly increases the involvement of almost all students in active communication activities in the classroom. Communication activity in the implementation of social and educational interaction between small and large groups made it possible to most effectively form professional socialization among students. Statistical analysis showed that it was classes in a remote format using video conferencing in subgroups of 4‒5 students that had the greatest positive effect. Discussion and Conclusion. The conclusions made by the authors contribute to the development of new forms of effective communication through social and educational interaction in the implementation of video conferencing. The materials of the article can be useful in the implementation of teacher education to increase the level of studentsʼ involvement in professional training in the context of distance education.